A facile approach for the synthesis of copper(ii) myristate strips and their electrochemical activity towards the oxygen reduction reaction. Issue 19 (8th February 2016) - Mukherjee, Indrani; Samantara, Aneeya K.; Ratha, Satyajit; Singh, Bimal P.; Jena, Bikash Kumar; Chatterjee, Sriparna
Abstract : Copper(ii ) myristate strips, an inexpensive, straight chain compound of copper act as active electrocatalyst in oxygen reduction reaction. Abstract : The usage of an inexpensive and non-noble metal-based material as the electrocatalyst in the oxygen reduction reaction has gained great attention for fuel cell application. In this report, a facile approach has been developed for the synthesis of copper myristate strips. The as-synthesized material has demonstrated its electrocatalytic activity towards oxygen reduction reaction. This study opens up a new scope for the use of straight chain copper complexes as electrocatalysts. The interesting performance of the copper myristate strips holds promising application in energy conversion devices.